Morphological Error in Students’ Recount Text - Liani, Ghustiva (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
The objective of this research was to know, describe and interpret the morphological error in recount text made by students of a Private Junior High School in North Jakarta. The population in this research is the students of grade VIII at the school. The method used in this study is descriptive analysis method to describe students’ errors consisting of 28 erroneous sentences and analyze the data taken from written test. The classification of errors in this research is divided into four categories; they are omission, addition, misformation, and disordering. The findings showed that the number of errors in morphological level, committed by the students are in inflectional morphology as much as 22 (79%) and derivational morphology is 6 (21%). It happened because students’ lack of understanding in applying the parts of speech in the sentences, such as verb, to be, preposition, pronoun, noun, conjunction, adverb, adjective and others. Thus, students find it difficult to arrange or form one word along with its meaning. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui, mendeskripsikan, dan menginterpretasikan kesalahan morfologis dalam “recount text” yang dibuat oleh para siswa di salah satu sekolah SMP swasta di Jakarta Utara. Populasi dalam penelitian ini adalah siswa kelas VIII di sekolah tersebut. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif untuk menggambarkan kesalahan siswa yang terdiri dari 28 kalimat yang mengandung kesalahan, serta menganalisis data yang diambil dari tes tertulis. Klasifikasi kesalahan dalam penelitian ini dibagi menjadi empat kategori, yaitu penghilangan, penambahan, pembentukan yang salah, dan penyusunan yang salah. Temuan menunjukkan bahwa jumlah kesalahan pada tingkat morfologis yang dilakukan oleh para siswa di sekolah tersebut terdapat pada morfologi infleksional sebanyak 22 kesalahan (79%) dan morfologi derivasional sebanyak 6 kesalahan (21%). Hal ini terjadi karena kurangnya pemahaman siswa dalam menerapkan kelas kata (parts of speech) dalam kalimat, seperti kata kerja, kata kerja bantu (to be), preposisi, pronomina, kata benda, konjungsi, kata keterangan, kata sifat, dan lainnya. Akibatnya, siswa mengalami kesulitan dalam menyusun atau membentuk suatu kata beserta maknanya.